Aspects of the bioavailability of topical corticosteroid formulations - Magnus, Ashley Denis (Rhodes University, Faculty of Pharmacy, Pharmacy, 1979)
Two possible variables of the McKenzie/Stoughton blanching assay, namely amount applied to the test site and occlusion time have been investigated. Subsequently, two topical steroid preparations, Synalar cream (0,025% fluocinolone acetonide) and Betnovate cream (0,1% betamethasone 17- valerate) were extemporaneously diluted with five and six placebo bases respectively. Taking cognizance of the two possible variables, these diluted preparations were assessed in vivo using a modified version of the McKenzie/Stoughton blanching assay for blanching activity over a 14 month period. It was found that the base E45, which is slightly alkali, had the greatest effect on both preparations. In the case of betamethasone 17-valerate this base caused the conversion to the less active isomer, betamethasone 21-valerate whereas at the end of the 14 month test period it was found that the Synalar/E45 dilution contained no fluocinolone acetonide. Quantitative analysis of all the diluted preparations by high performance liquid chromatography using a reverse-phase system was performed. The data obtained from the systematic studies of the effects of varying concentrations and occlusion times were presented at the Eleventh National Congress of the South African Pharmacological Society
Keywords: Adrenocortical hormones; Dermatopharmacology; Dermatologic agents; Transdermal medication